ГОТОВНІСТЬ ДО КРАЄЗНАВЧОЇ ОСВІТИ: ЗМІСТ ТА СТРУКТУРА (Педагогіка вищої та середньої школи, 2007)
The different approaches in disdinguishing the structure of the students' readiness for teachers activity are analysed in the article. On the base of this analises the author distinguishes the structural components which form the future teachers readiness for the local lore activity.